2013
DOI: 10.1111/aab.12022
|View full text |Cite
|
Sign up to set email alerts
|

Horticultural mineral oil treatments in nurseries during aphid flights reduce Plum pox virus incidence under different ecological conditions

Abstract: The application of horticultural mineral oil (HMO) treatments has been reported as a possible control strategy to reduce Plum pox virus (PPV) incidence in Prunus nurseries. The effect of Sunspray Ultrafine HMO at 1% on the natural viral spread was evaluated in experimental nursery plots of Nemaguard and Mariana GF8-1 Prunus rootstock blocks established under high natural inoculum pressure of the most prevalent PPV-types. Tests were conducted in experimental nursery plots in Plovdiv, Bulgaria (PPV-M and PPV-Rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Infections starting with a completely random spatial pattern which finally reaches a uniform distribution in the orchard have also been reported (Varveri, ). The application of horticultural mineral oil has been shown to be an efficient control strategy to reduce PPV incidence in nursery plots (Vidal et al ., ).…”
Section: Epidemiology and Transmissionmentioning
confidence: 97%
“…Infections starting with a completely random spatial pattern which finally reaches a uniform distribution in the orchard have also been reported (Varveri, ). The application of horticultural mineral oil has been shown to be an efficient control strategy to reduce PPV incidence in nursery plots (Vidal et al ., ).…”
Section: Epidemiology and Transmissionmentioning
confidence: 97%
“…A few examples of other original contributions from the many published in the journal over the last 100 years relevant to the theme of plant virus ecology and epidemiology include:‐ Virus spread by aphid (Broadbent, ; Watson et al ., , ; Elnagar & Murant, ; Tatchell et al ., ); whitefly (Fargette et al ., ), leafhopper (Soleimani et al ., ), mite (Thresh, ), nematode (Harrison, ) and fungus (Rosner et al ., ) vectors; Virus spread by contact (McKirdy et al ., ); Seed transmission of nematode‐borne (Lister & Murant, ; Murant & Lister, ; Hanada & Harrison, 1977), aphid‐borne (Jones, 1988 b ; Jones & Proudlove, ), and contact‐transmitted viruses (Wroth & Jones, ); Weeds as virus reservoirs (Tomlinson et al ., ; Ramappa et al ., ; Pallett et al ., 2002); Virus or vector resistance deployment (Jones, ; Ferris et al ., ); Virus resistance breakdown (Pelham et al ., ; Thomas‐Carroll & Jones, ); Effects of cultural practices on spread of aphid‐borne viruses (Kendall et al ., ; Jones, , ; Difonzo et al ., ; Sauke & Doring, ); Control of aphid‐borne viruses by insecticides (Jones & Ferris, ) or mineral oil (Vidal et al ., ); Control of nematode‐borne viruses by nematicides (Harrison et al ., ); Control of fungus‐transmitted viruses by fungicides (Tomlinson & Faithfull, ); Forecasting virus epidemics (Harrington et al ., ). …”
Section: Annals Of Applied Biology Research Papersmentioning
confidence: 99%
“…Overall, the control of aphid populations is very important in order to reduce the direct damages, and to limit the spread of PPV which produces significant additional losses. Previous field studies have shown that the application of mineral oils, which are accepted in ecological farming, is useful in reducing the incidence of PPV infections [ 16 ]. The allelopathic effect of phenolic acids can also be a good tool for protecting plants against aphid infestation; a high concentration of phenolic acid (gallic acid and caffeic acid) inflicts a reduction in aphid infestation [ 17 ].…”
Section: Introductionmentioning
confidence: 99%